How daily supervisor abuse and coworker support affect daily work engagement - Wang, Hongqing; Tang, Tianzhen (Frontiers in Psychology, 2022)
The purpose of this study was to explore the dynamic and intervention mechanisms of daily abusive experience affecting daily work engagement. Drawing on conservation of resources (COR) theory, we examine the effect of daily abusive supervision on daily work engagement through daily negative emotions from the resource consumption perspective, and the moderation effect of coworker support from the resource provision perspective. Using a daily diary approach and based on a sample of 73 employees for 5 consecutive days in China. The results reveal that daily abusive supervision has a significant negative effect on daily work engagement, daily negative emotions mediate this relationship, and coworker support had a cross-level moderating effect between daily abusive supervision and daily negative emotions. Our study shows ways to boost employees’ daily work engagement and especially ways buffer the negative effect of abused experience on work engagement.